2007
DOI: 10.1562/2006-06-16-ra-930
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Tuning of Photoactive Yellow Protein†

Abstract: We report a theoretical study on the optical properties of a small, water-soluble photosensory receptor, photoactive yellow protein (PYP). A hierarchical ab initio molecular orbital calculation accurately evaluated the optical absorption maximum of the wild-type, as well as the lambda(max) values of 12 mutants. Electronic excitation of the chromophore directly affects the electronic state of nearby atoms in the protein environment. This effect is explicitly considered in the present study. Furthermore, the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…Substitution mutations at the residue under study in principle can affect three independent properties of the S 0 and S 1 energy surfaces: ΔE, R e , and W. The expected consequences of changes in these three properties can be formulated as described below. The electronic structure of PYP has been examined by a number of computational studies (24)(25)(26)(27), but the details of the shape of the S 0 and S 1 energy surfaces and Franck-Condon factors for the pCA in its active site are difficult to obtain with high accuracy. However, general trends in changes in the position and shape of the absorbance and emission fluorescence maxima as a result of changes in ΔE, R e , and W can be derived.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Substitution mutations at the residue under study in principle can affect three independent properties of the S 0 and S 1 energy surfaces: ΔE, R e , and W. The expected consequences of changes in these three properties can be formulated as described below. The electronic structure of PYP has been examined by a number of computational studies (24)(25)(26)(27), but the details of the shape of the S 0 and S 1 energy surfaces and Franck-Condon factors for the pCA in its active site are difficult to obtain with high accuracy. However, general trends in changes in the position and shape of the absorbance and emission fluorescence maxima as a result of changes in ΔE, R e , and W can be derived.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental and computational work on PYP has confirmed that the chromophore absorbance band at 446 nm is a π-π Ã transition, has identified Glu46 and Tyr42 as the main contributors to the effect of the protein on the pCA absorbance spectrum, and has revealed that the hydrogen bonding interactions between these two side chains and the pCA are critical for spectral tuning in PYP (18)(19)(20)(21)(24)(25)(26)(27). These studies have all focused on the energy gap between the S 0 and S 1 states, i.e., ΔE-tuning.…”
Section: Correlating Fluorescence Quantum Yield and Excited State Lifmentioning
confidence: 99%
See 2 more Smart Citations
“…Calculations of the absorption maxima of various PYP mutants have been presented in refs. [251,252]. These studies employed a partitioning scheme similar to ONIOM, in which the fragment molecular orbital method was employed as a lowlevel QM approach in combination with CASPT2 as a high-level approach.…”
Section: Pypmentioning
confidence: 99%